STRUGGLE IN H. G. WELLS’ NOVEL THE ISLAND OF DOCTOR MOREAU - Yudi Kurniawan; Muhammad Fatih Suhadi (JOURNAL OF LANGUAGE, 2021)
This study constitutes an identification of the protagonist’s struggle in H. G. Wells’ novel The Island of Doctor Moreau. This study discusses the story of an English shipwreck survivor named Edward Prendick who is rescued from an accident and taken to an unnamed island to be mended by Montgomery. He is a man of science who works for Doctor Moreau in the island. The story deals with Prendick’s struggle to maintain his sanity due to Doctor Moreau terrifyingly peculiar works of vivisection practices. This study focuses on Doctor Moreau through Prendick’s point of view. Prendick, as the protagonist, experiences both internal and external struggle. He has to choose between saving his life or to obey Dr. Moreau to do his evil bidding. Otherwise, he has to keep his composure to blend with the island people. This study adopts descriptive qualitative method to characterise the mental struggle experienced by the protagonist. The study concludes that the protagonist experiences significant amount of both internal and external struggle throughout the story. The recommendation of this story is a moral lesson. The lesson is to face struggle head-on so you can defeat it. Hopefully, this study can be of relevance in future studies regarding the topic discussed in this study.